A contribution to the dynamic simulation of robot manipulator with the software RobotDyn - Khang, Nguyen Van; Tung, Do Thanh (Vietnam Journal of Mechanics, 2004)
Robots manipulators are multibody systems with tree structures. In this paper the theoretical background of the computer program RobotDyn is presented. The program is developed using Lagrange’s equations and Denavit-Hartenberg matrix. The dynamic simulation of the Robot SCARA with four degrees of freedom is considered as an example of application of the program RobotDyn.